FACTORS AFFECTING VILLAGE FINANCIAL ACCOUNTABILITY IN VILLAGE GOVERNMENT IN SERDANG BEDAGAI REGENCY - nada, naimah (International Journal of Public Budgeting, Accounting and Finance, 2018)
The objective of the research was to find out, analyze, and prove empirically some factors which influenced Village Financial Accountability in Serdang Bedagai District Administration. The research used associative causal method. The population was 237 villages in Serdang Bedagai Regency and the samples were 38 villages, consisted of 38 village heads, 38 village secretaries,and 38 village treasurers (total of 114 respondents). Primary data were gathered by using questionnaires and analyzed by using multiple linear regression analysis. The result of the research showed that, simultaneously, Financial Management, Quality of Human Resources, Supervision, and Public Participation had significant influence on Village Financial Accountability in Serdang Bedagai District Administration. Partially, Quality of Human Resources, Supervision, and Public Participation had significant influence, while Financial Management did not have any influence on Village Financial Accountability in Serdang Bedagai District Administration.